(untitled) (Sciences & Technology. A, exactes sciences, 2003)
The attractive potential energy between the atoms of rubidium vapor and a dielectric wall has been investigated by monitoring the reflection light at the interface. The atom- wall interaction potential of the form V(z) = - C /z3 (z: atom-wall) allows to predict experimental results only for weak regime, i.e., where C<< 0.2 kHzmm3. In the strong interaction case, the dispersive line shape is turned into an absorption-type line shape. The influence of atomic density on the shift of the selective reflection resonance relatively to the frequency of unperturbed atomic transition is found to be red with a negative slope. This technique opens the way to characterize the windows made of different materials thin films.